2009
DOI: 10.2460/ajvr.70.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of equine tendon-, muscle-, and bone marrow–derived cells cultured on tendon matrix

Abstract: Objective-To compare viability and biosynthetic capacities of cells isolated from equine tendon, muscle, and bone marrow grown on autogenous tendon matrix. Sample Population-Cells from 4 young adult horses. Procedures-Cells were isolated, expanded, and cultured on autogenous cell-free tendon matrix for 7 days. Samples were analyzed for cell viability, proteoglycan synthesis, collagen synthesis, and mRNA expression of collagen type I, collagen type III, and cartilage oligomeric matrix protein (COMP). Results-Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…25 However, our own unpublished data showed that this procedure, although reducing the content of vital cells, did not remove DNA, which was recently supported by others. 18 Freeze-thaw cycles with subsequent nuclease treatment led to nearly complete removal of cells and DNA, 18 but nuclease treatment was performed on sliced tendon only, 18,21 thus, this protocol does not appear applicable for decellularization of whole, large tendon constructs.…”
Section: Introductionmentioning
confidence: 64%
“…25 However, our own unpublished data showed that this procedure, although reducing the content of vital cells, did not remove DNA, which was recently supported by others. 18 Freeze-thaw cycles with subsequent nuclease treatment led to nearly complete removal of cells and DNA, 18 but nuclease treatment was performed on sliced tendon only, 18,21 thus, this protocol does not appear applicable for decellularization of whole, large tendon constructs.…”
Section: Introductionmentioning
confidence: 64%
“…29,59,75 Other autologous cell sources, including adipose tissue, muscle, synovium, periosteum, tendon-derived stem cells, dermal fibroblasts, and stem cells derived from umbilical cord or peripheral blood, have all been evaluated as sources of multipotent and pluripotent cells. 19,97,120,129,141,144 Adipose-derived stem cells are relatively easy to harvest, and selection of adherent cells over the course of several weeks in monolayer culture provides a cell type that improves the healing potential of flexor tendons. 129 Similarly, stem cells derived from skeletal muscle have been used in a variety of musculoskeletal repair indications and are readily harvested and propagated before reimplantation.…”
Section: Mesenchymal Stem Cells Definitionmentioning
confidence: 99%
“…MSCs were isolated from bone marrow aspirate harvested from the sternum of a one year old male horse, euthanized for unrelated conditions, following approval of the Institutional Animal Care and Use Committee (IACUC) of the Virginia Polytechnic Institute and State University and assessed via previously described techniques [28]. Briefly, bone marrow was collected, centrifuged to remove the plasma, and cultured in media containing low-glucose GlutaMAX DMEM with 110 mg/mL sodium pyruvate (Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 10% MSCs fetal bovine serum (Thermo Fisher Scientific, Waltham, MA, USA), and 1% sodium penicillin and streptomycin sulfate (Sigma, St. Louis, MO, USA) at 37 • C, 5% CO 2 and 90% humidity.…”
Section: Isolation and Characterization Of Primary Equine Mesenchymalmentioning
confidence: 99%